Penatalaksanaan Fisioterapi Pada Kasus Post Stroke Hemiparese Non Haemoragik Dextra Di RST Dr Soedjono - Hananta Wisnu W, Rio; , Agus Widodo, S.Fis, M.Kes (2016)
Background: Stroke non haemoragic is the most of stroke from all type stroke. This type happen because a lump at artery and flow to brain. The writer use bridging exercise, stretching wrist, and Proprioceptive Neuromuscular Facilitation (PNF) method for this case to superintend spastisitas , strength of muscle, coordination, balance, and activity daily living. Objective: To know benefit of bridging exercise, stretching wrist, and PNF method for this case to superintend spastisitas, strength of muscle, coordination, balance, and activity daily living. Results: After treatment for 5 times, we found decrease of spastisitas flexor wrist from T1 : 2 to T5 : 1. At assessment of balance, total score from T1: 44 to T5: 46. At assessment strength of muscle with MMT, the result at flexor shoulder, ekstensor shoulder, adductor shoulder and abductor shoulder T1: 3 to T5: 4, at regio supinator and pronator T1: 3 to T5: 4. At asessment activity daily living total score T1: 90 to T5: 95. And then, at assessment coordination with coordination non equilibrium total score T1: 58 to T5: 60. Conclusion: After treatment for 5 times, we found decrease of spastisitas, increase assessment of balance, increase strenght of muscle, increase assessment activity daily living, and increase of coordination. Keywords: Stroke non haemoragik, bridging exercise, stretching wrist, Proprioceptive Neuromuscular Facilitation (PNF), spastisitas ,berg balance scale, MMT index barthel, and coordination non equilibrium.